IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS AUDIO-VISUAL DALAM PEMBELAJARAN AL-QUR’AN HADIST DI SEKOLAH MENENGAH PERTAMA - Muhamad Iqbal; Isfihani Isfihani; Iffah Mukhlisah (STKIP Pesisir Selatan, 2026)
The rapid development of digital technology has encouraged the integration of audio-visual learning media in educational practices, including in Al-Qur’an Hadith instruction. This study aims to explore the implementation of audio-visual learning media in teaching Al-Qur’an Hadith at SMP Muhammadiyah 2 Boyolali Program Khusus, focusing on the stages of planning, implementation, evaluation, as well as identifying challenges and practical solutions. This research employed a qualitative descriptive approach with a case study design. Data were collected through classroom observations, in-depth interviews, and documentation, while data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña, involving data reduction, data display, and conclusion drawing. The findings indicate that the use of audio-visual media significantly enhances students’ learning motivation, engagement, and conceptual understanding, particularly in tajwid mastery and hadith comprehension. This study contributes to the development of multimedia-based learning practices in Islamic education and offers practical insights for improving the quality and effectiveness of Al-Qur’an Hadith instruction in junior high schools.